EVALUATION AND COMPARISON OF MANUAL DEXTERITY IN CHILDREN WITH DOWN SYNDROME AND NEUROTYPICAL DEVELOPMENT: CASE REPORT - Souza, Larah Vitória Alves de; Fonseca, Daniela Rosana Pedro; Lopes, Jamile Benite Palma; Oliveira, Cláudia Santos (CIPEEX, 2025)
Objective: To evaluate and compare manual dexterity using the Box and Block Test in children with Down syndrome and neurotypical development. Methodology: This is a case report in which the manual dexterity of one child with Down syndrome and one neurotypical child was evaluated and compared.Results: The comparison revealed that both children were more agile with their non-dominant hand. The child with Down syndrome (DS) manipulated 29 blocks with the dominant hand and 33 blocks with the non-dominant hand, while the neurotypical child manipulated 50 blocks with the dominant hand and 58 blocks with the non-dominant hand.Conclusion: It was concluded that both children, with DS and neurotypical development, showed greater agility with the non-dominant hand. However, the neurotypical child demonstrated superior performance, manipulating more blocks with both hands.